Evaluating the Effectiveness of Electrocardiological Study Using Cardiological Decision Support Systems - Filatova, A. E.; Skarga-Bandurova, Inna; Brezhniev, Eugene; Fahs, Mohamad (My University, 2020)
This work is devoted to evaluating the effectiveness of the electrocardiological study process without using and using cardiological decision support systems. To assess the effectiveness, analytical expressions of the probabilistic-time characteristics of the developed structural model of the electrocardiological study process are used. An analysis of the time characteristics of the model is performed when different initial conditions are set for three different types of electrocardiological studies: the study is conducted for the first time, the study is repeated as a result of screening, the study is repeated after treatment. The work shows that the use of cardiological decision support systems based on the developed methods for analyzing biomedical signals with locally concentrated features reduced the average time required for the electrocardiological study of each of the considered types.
Keywords: electrocardiological study; cardiological decision support system; probabilistic-time characteristic; biomedical signals with locally concentrated features